An enhanced architecture of online 3D visualization framework for monitoring coconut plantation - Saha, Gonesh Chandra (2020)
The visualization of existing and future agricultural plantation is becoming more important for monitoring crops as well as for decision-making, as it considerably helps to influences the production. The concept of best monitoring coconut plantation is an important stage of agricultural technology development; for instance, utilizing online 3D visualization system to support monitoring processes. The goal of this research is to present and justify an identified research problem with the utilization of a proposed enhanced architecture of online 3D visualization framework. The identified research problem was investigated since the current 3-layer framework has shortcomings, such as, weaknesses in the size of graph visualization, especially the ability to visualize large size of graph in online 3D visualization. In such situation, 3D visualization seems challenging as it generates a massive amount of image datasets and large 3D objects or graphs for each of the coconut trees. Therefore, in this novel approach, this study introduced a client/server structure-based framework which subdivides the total process into the concept of layer to overcome the existing issue. One more layer will be added to the existing three-layer framework to formalize into 3-layer framework for handling the large size graph visualization. It consists of four separate layers, namely interface layer, visualization process layer, display information layer, and database layer. Each layer has its own specific function and distinct from others. The framework was reviewed, evaluated and validated by the coconut plantation manager and 3D visualization experts; it was then used as a basis to develop a prototype to visualize the large virtual area of coconut plantation. Subsequently, the prototype was evaluated by users with diverse experience. Overall, results from the usability testing demonstrated that it can comfortably support or handle more graphs of the coconut plantation, thus achieving its satisfaction through formulating identified graph visualization problem.